The Alterations of Mitochondrial Function during NAFLD Progression-An Independent Effect of Mitochondrial ROS Production - Simões, Inês C M (2021)
The progression of non-alcoholic fatty liver (NAFL) into non-alcoholic steatohepatitis implicates multiple mechanisms, chief of which is mitochondrial dysfunction. However, the sequence of events underlying mitochondrial failure are still poorly clarified. In this work, male C57BL/6J mice were fed with a high-fat plus high-sucrose diet for 16, 20, 22, and 24 weeks to induce NAFL. Up to the 20th week, an early mitochondrial remodeling with increased OXPHOS subunits levels and higher mitochondrial respiration occurred. Interestingly, a progressive loss of mitochondrial respiration along "Western diet" feeding was identified, accompanied by higher susceptibility to mitochondrial permeability transition pore opening. Importantly, our findings prove that mitochondrial alterations and subsequent impairment are independent of an excessive mitochondrial reactive oxygen species (ROS) generation, which was found to be progressively diminished along with disease progression. Instead, increased peroxisomal abundance and peroxisomal fatty acid oxidation-related pathway suggest that peroxisomes may contribute to hepatic ROS generation and oxidative damage, which may accelerate hepatic injury and disease progression. We show here for the first time the sequential events of mitochondrial alterations involved in non-alcoholic fatty liver disease (NAFLD) progression and demonstrate that mitochondrial ROS are not one of the first hits that cause NAFLD progression.